WebDAV: Next-Generation Collaborative Web Authoring - Dusseault, Lisa (Prentice Hall series in computer networking and distributed systems., 2003)
WebDAV: Next-Generation Collaborative Web Authoring is the complete guide to Web-based Distributed Authoring and Versioning (WebDAV), the IETF standard for Web authoring and wide area collaboration. Experienced implementer Lisa Dusseault covers WebDAV from bits on the wire up to custom application implementation, demonstrating with extensive examples and traces from real clients and servers. Coverage includes: practical rules for building WebDAV document management systems; step-by-step, Internet Explorer compatible sample applications; and the latest WebDAV tools. For application designers, software engineers, and information managers.